ISO 9001 and Academic Management for University Entities - Moquillaza Henríquez, Santiago (2017)
The ISO 9001 standards in different versions 2008 and 2015, serve the organizations to implement a Quality Management System so that they can create products or provide quality services for the client or end user. As the universities providing educational services, having to train students of quality in this changing competitive environment, they can not manage their business processes in an inorganic way, that is, with chaotic processes. The present article presents a development model applying the ISO 9001 standards, seeking to influence the satisfaction of the academic coordinators of the Faculty of Administrative Sciences of the University object of study, and expecting impact in turn in the satisfaction of the students, in Basis of a recurrent process of continuous improvement.